Miri City Council Sarawak / Trena Majang - Majang, Trena (University Technology MARA Sarawak, 2019)
Miri City Council (Majlis Bandaraya Miri) which is under Ministry of Local Government and Housing Sarawak. The establishment of the Council may be traced back to the early 1930s. In 1933, the Miri Municipal Board was established following the enactment of the Municipal Order No. M-7,1933. The Board consisted of the Resident, 4th Division as Chairman, together with the Municipal Officer and a few community leaders as members. It continued to function up to December, 1941 when it was interrupted by Japanese Occupation until 1945. On 1st January, 1956 the Miri Municipal Board was re-constituted and became the Miri Urban District Council, financially self-supporting and managing its own local affairs. The Council consisted of 17 members, all of whom were nominated. In December, 1960 a Council's general election was held for the first time in Miri. The fully elected Council constituted under the Local Authority (Miri District Council) Order 1960, began functioning on 9th January, 1961. Under the new constitution, the Council was changed from the Urban District Council to the status of a District Council in order to meet the requirements of new development in the field of local government, and with the object of extending its boundaries to include the whole of the Miri administrative sub-district. The Council consisted of 18 elected members. The Divisional Engineer, the Superintendent of Lands and Surveys, the Divisional Medical Officer, the Divisional Education Officer and the Superintendent of Police were advisers to the Council. The second Council's general election was held in May/June, 1963. The district was divided into 14 electoral wards with 19 members. Five of the 19 members were elected to the Divisional Advisory Council. The Council area of jurisdiction then was 337 square miles, with a population of 24,049, based on the 1960 Census Report. Following the restructuring of local authorities in the State in 1981, the Miri District council was upgraded into a Municipality and the new Councillors were sworn in on 6th November, 1981. The newly restructured Miri Municipal Council consisted of a Chairman, a Deputy Chairman and 24 Councillors, all of whom were nominated.